Real-time mechanism-based interventions for daily alcohol challenges: protocol for ecological momentary assessment and intervention : research protocol - Liu, Shuyan; Haucke, Matthias; Groß, Rika Maria; Schneider, Kay; Shin, Jaekyung; Arntz, Fabian; Bach, Patrick; Banaschewski, Tobias; Beste, Christian; Deserno, Lorenz; Ebner-Priemer, Ulrich; Endrass, Tanja; et al. (Digital health, 2025)
Background - Advancing evidence-based, tailored interventions for substance use disorders (SUDs) requires understanding temporal directionality while upholding ecological validity. Previous studies identified loneliness and craving as pivotal factors associated with alcohol consumption, yet the precise directionality of these relationships remains ambiguous. - Objective - This study aims to establish a smartphone-based real-life intervention platform that integrates momentary assessment and intervention into everyday life. The platform will explore the temporal directionality of contextual influences on alcohol use among individuals experiencing loneliness and craving. - Methods - We will target 180 individuals aged 18 to 70 in Germany who report loneliness, alcohol cravings, and meet risk or binge drinking criteria (over 14 standard drinks per week or five drinks in a single day for males, and over seven drinks per week or four drinks in a single day for females). Using a Within-Person-Encouragement-Design and Just-In-Time-Adaptive-Interventions, we will manipulate the contexts of loneliness and alcohol craving with cognitive reappraisal and physical activity interventions against a control condition (working memory task). - Results - Recruitment started in June 2024, with data collection and processing expected by June 2027. - Conclusion - Our real-life intervention platform endeavors to serve as a robust tool for discerning the directionality of the effects from time series data in everyday life influences on alcohol use for the future study. Ultimately, it will pave the way for low-threshold prevention, clinical treatment, and therapy to target diverse contexts of everyday life in SUD. - Trial registration - German Clinical Trials Register DRKS00033133.